Assessing institutional empathy in medical settings. Issue 1 (17th January 2018) - Atkins, Sarah; Roberts, Celia
Abstract : The use of role-play in standardised medical assessments raises many problems, particularly around the measurement of interpersonal skills such as 'empathy'. Research on the use of simulations has tended to focus on quantified, psychometric assessments of their reliability and validity. However, communication, which often forms a central part of the assessment in medical simulations, is a difficult matter to address through this post hoc analytic method. A sociolinguistic approach to analysing real recordings of simulated medical assessments allows greater insight into communication and interpersonal skills. We use our research on medical licensing exams to illustrate some of the current questions about the examining of such skills through understanding the fine-grained detail of talk. Drawing on Goffman to critique simulated relationships and on Gumperz to analyse the role of differences in communicative style, and based on microanalysis of video-recorded role-players and candidates, we argue that the focus on interpersonal skills in standardised assessments amplifies the problem of using simulated empathy and requires additional interactional work. This focus on interpersonal skills in such assessments can lead to inequalities, since an unfair weight may be put upon candidates trained overseas. The paper concludes that the debate on 'language' in such exams and their standardisation in superdiverse societies needs to be reset. CC-BY - This work is licensed under https://creativecommons.org/licenses/by/4.0/